2015
DOI: 10.1002/hed.23834
|View full text |Cite
|
Sign up to set email alerts
|

Laryngeal cancer in Finland: A 5‐year follow‐up study of 366 patients

Abstract: Results of this nationwide study give a general overview of the outcome of unselected patients treated with unified guidelines. Patients with T2 tumors, usually treated with radiotherapy (RT), had a worse prognosis than expected. This patient group warrants further investigation and possibly treatment intensification.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
58
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(68 citation statements)
references
References 36 publications
7
58
3
Order By: Relevance
“…Although overall survival rate for our entire cohort of patients was excellent, it was concerning to see overall survival of patients with T2N0 (Stage II) cancers to be similar to those with Stage IV cancer (Figure 2). Similar unsatisfactory survival rates for patients with T2 cancers have been reported recently in a large nationwide study of unselected patients in Finland 68 . To better understand these results, detailed analysis of our relatively small number of T2 larynx cancer patients (N= 34) is underway.…”
Section: Discussionsupporting
confidence: 87%
“…Although overall survival rate for our entire cohort of patients was excellent, it was concerning to see overall survival of patients with T2N0 (Stage II) cancers to be similar to those with Stage IV cancer (Figure 2). Similar unsatisfactory survival rates for patients with T2 cancers have been reported recently in a large nationwide study of unselected patients in Finland 68 . To better understand these results, detailed analysis of our relatively small number of T2 larynx cancer patients (N= 34) is underway.…”
Section: Discussionsupporting
confidence: 87%
“…Laryngeal carcinoma is predominantly a cancer of men and is rare in women 20, 43 . We adjusted other risk factors to avoid potential bias and found that the relative abundances of Streptococcus and Fusobacterium were reduced and enriched, respectively, in the larynx of male laryngeal cancer patients.…”
Section: Discussionmentioning
confidence: 99%
“…Laryngeal carcinoma is one of the most common malignancies of the head and neck, and squamous cell carcinoma is the most frequent histological type of laryngeal carcinoma, accounting for 98% of cases 19, 20 . The main risk factors for this cancer include tobacco smoking and alcohol consumption, and the roles of these risk factors have been consistently confirmed by a growing number of studies 21, 22 .…”
Section: Introductionmentioning
confidence: 99%
“…LSCC has three subsites: supraglottic, glottic, and subglottic tumors [4]. Glottic squamous cell carcinoma (GSCC) originates from the true vocal cords, and approximately 51% of LSCCs are glottic primary tumors, of which 85% to 95% are GSCC [5].…”
Section: Introductionmentioning
confidence: 99%